2004
DOI: 10.2223/1190
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive breastfeeding at the point of discharge of high-risk newborns at a Neonatal Intensive Care Unit and the factors associated with this practice

Abstract: Este trabalho é parte da Dissertação de Mestrado defendida por Paula G. Bicalho-Mancini junto ao Curso de Mestrado em Enfermagem, UFMG.Artigo submetido em 19.12.03, aceito em 03.03.04. AbstractObjective: To study the rate of exclusive breastfeeding at the moment of hospital discharge of newborns admitted to a neonatal Intensive Care Unit and to analyze potential risk factors.Methods: Four hundred and ninety-five medical records were studied, pertaining to neonates born between 1998 and 1999, admitted to a neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 4 publications
1
25
2
3
Order By: Relevance
“…Low birth weight of premature infants might have contributed to this result as well. Although there are studies that report no significant association between birth weight and breast-feeding duration (28,29) , the present study together with some others reveal that low birth weight has a negative impact on duration of breast-feeding (5,8,20,30) .…”
Section: Duration Of Breast-feedingcontrasting
confidence: 74%
“…Low birth weight of premature infants might have contributed to this result as well. Although there are studies that report no significant association between birth weight and breast-feeding duration (28,29) , the present study together with some others reveal that low birth weight has a negative impact on duration of breast-feeding (5,8,20,30) .…”
Section: Duration Of Breast-feedingcontrasting
confidence: 74%
“…Likewise, Espy and Senn [30] reported that preterm NICU infants who breast-feed consistently were more likely to have older mothers. Conversely, Bicalho-Mancini and Velásquez-Meléndez [57] found no significant difference in the prevalence of exclusive breastfeeding at NICU discharge between adolescent and older mothers. Although the studies by Lessen and Crivelli-Kovach [32], Purdy et al [25], and Espy and Senn [30] were completed in the United States, the study by BicalhoMancini and Velásquez-Meléndez [57] was completed in Brazil.…”
Section: Resultsmentioning
confidence: 89%
“…There were also notable methodological issues in these studies. For example, retrospective data collection methods of telephone survey [32] and chart review [57,58] might have led to recall and reviewer biases respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Many factors have the potential to influence whether a mother successfully breastfeeds their very preterm infant. Factors associated with a greater proportion of preterm babies successfully breastfeeding include older maternal age [20][21][22] ; early initiation of breastfeeding 23 ; higher parity 21,[24][25][26] ; higher socio-economic and educational status 20,21,24,27 ; marital status as married 28 ; and a range of practices including skin-to-skin post delivery, 29 implementation of the Baby Friendly Hospital Initiative, [30][31][32] maternal breastfeeding education, bedside nursing and lactation practitioners support, 21,22,29,[33][34][35][36][37][38] the practice of kangaroo mother care, 32,39-41 the use of pacifiers and lullabies 42 and the practice of pre-feed oral stimulation. 43 Conversely, factors associated with a smaller proportion of preterm babies successfully breastfeeding include prematurity and low birthweight, 20,21,25,32,[44][45][46] prolonged length of hospital stay, 20,21,25,26,44,45 multiple pregnancy, 20 chronic neonatal lung dis...…”
Section: Discussionmentioning
confidence: 99%